Postcolonialism in Hamid’s The Reluctant Fundamentalist - Hira Ali; Naila Khadim; Aisha Umer (Al-Qanṭara, 2024)
The Reluctant Fundamentalist by Mohsin Hamid is examined in this study using a post-colonialist perspective. The purpose of the study is to examine the major characters from these two novels within the framework of postcolonial theory, taking into consideration the influences of racism, identity, and otherness on Changez and Ander's personalities. The study chooses for a qualitative methodology and applies the descriptive analytical method to analyze the various characters in the book, such as Oona's mother, Eric, and Ander's father. The works of postcolonial literary critics like Homi K. Baba's Sign Taken for Wonders and The Real Me, Leela Gandhi's Postcolonial Theory: A Critical Introduction, Frantz Fanon's Black Skin White Masks, and Edward Said's Orientalism have all been carefully read and referenced in this work. Verbal data, such as texts, is employed for the purpose of the fundamental analysis and solving of the study problems. The Last White Man and The Reluctant Fundamentalist by Hamid successfully illustrate postcolonial concerns of identity, otherness, and racism, according to the findings. The protagonists of these stories can be used to identify identity as a construction process that follows colonization. In an effort to interpret tradition and Europe as a part of their identity and as a framework of resistance against European control, the characters' viewpoints within their painful pasts could be seen as a critique of essentialism. This study can be used to analyze additional novels like Exit West from a postcolonial perspective in the future.